An extensive comparative analysis of successful and unsuccessful football teams in LaLiga - Brito de Souza, D.; Lopez-Del Campo, R.; Blanco-Pita, H.; Resta, R.; Del Coso, J. (Frontiers in Psychology, 2019)
The characterisation of the in-game actions with the strongest influence on victory in football might be useful for designing playing styles that enhance teams` performance. The aim of this study was to analyse in-game match statistics on the top-3 and bottom-3 teams ranked in LaLiga. Accumulated offensive and defensive match statistics when playing at home and away were obtained from LaLiga for 8 consecutive seasons. Data extraction was performed by computerised video-analysis. The top-3 and bottom-3 teams were compared using independent t-test analysis and the magnitude of the difference was catalogued with effect sizes. Overall, the offensive variable with the greatest magnitude of difference in the top-3 vs bottom-3 comparison was shooting accuracy (ES±90% confidence interval=4.15±0.52) followed by the number of offsides (2.25±0.60) and corners (2.14±0.61). However, when playing away, the offensive variable with the greatest magnitude of difference in the top-3 vs bottom-3 comparison was the number of shots (3.30±0.44). The defensive variables that best differentiated top 3 - bottom 3 teams were the number of corners (2.16±0.43) and shots conceded (2.04±0.39). In conclusion, the match statistics that best discriminated successful from unsuccessful football teams were shooting accuracy while attacking and the number of shots conceded while defending.